The Participation of Local Politic in West Sumatra: A Context of Indonesian Democracy Dynamic - Syafrizal, Syafrizal (TAWARIKH, 2009)
ABSTRACT: This article is concerned with the politic participation of West Sumatra people in the dynamic of Indonesian democracy. At the beginning of independence, there have seven political parties which were established in West Sumatra namely PERTI, MTKAAM, PKI Lokal Islami, MASYUMI, PNI and PSI. The establishment of the political parties is the reaction of local society to Governmentâs Advice on 3 November 1945 about the making of party to struggle for independence. Politic participation through political parties is very influential on the political development in West Sumatra. The activist of political parties to reform the leadership of ânagariâ (village) government, so that the role of âpenghuluâ (adat leaders) is liquidated in government affair because the people doubt of their nationalism. Their position replaced by the activist of the party in each ânagariâ. The liberty in the term of Liberal Democracy to result in a bad relationship between West Sumatra and central government, develop to become the movement of PRRI (1958-1961). Under the Guided Democracy of Soekarno (1959-1965) and the New Order of Soeharto (1966-1998), the politic participation is very limited in social life, include on the people of West Sumatra. KEY WORDS: politic participation, West Sumatera, local-central government relationship in Indonesia.Â About the Author: Syafrizal, M.Hum. is a Lecturer at the Department of History, Faculty of Letters UNAND (University of Andalas), Limau Manis UNANDâs Campus, Padang, West Sumatera, Indonesia. He can be reached at: syafrizal_2007@yahoo.co.idHow to cite this article? Syafrizal. (2009). âThe Participation of Local Politic in West Sumatra: A Context of Indonesian Democracy Dynamicâ in TAWARIKH: International Journal for Historical Studies, Vol.1(1) October, pp.97-106. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (August 10, 2009); Revised (September 13, 2009); and Published (October 28, 2009).